Estudo do envelhecimeto magnético em aços silício de grão não orientado 2%Si - Jose Rogerio de Oliveira Junior (2014)
In this work, the effect of ageing time and temperature on microstructure parameters, magnetic and mechanical properties of the 2%Si non-oriented electrical steel was studied. Cold rolled and annealed samples with 305x30x0,54mm and three different carbon contents 20, 32 and 46ppm were subjected to ageing treatments from 100 until 275ºC. During the ageing treatment, in each sample, the cycle was interrupted at varied time intervals in order to determine the core loss. After that, the characterization of the precipitates, in the all the aged samples, was performed in the scanning electron microscope (SEM). Based on the results of the ageing index changing along the time and in the metallographic analyses, the critical ageing temperature for each carbon content was determined. Then, samples with carbon content of about 32ppm were aged in the critical ageing temperature, in order to evaluate the microstructure parameters, magnetic and mechanical properties along the ageing time. The results have revealed that the core loss rise along the time, at given temperature, is cumulative and it is associated with carbide precipitation. Associated with the critical ageing temperature (180ºC) for carbon content 32ppm, a set of microstructural features, which implies in the maximal restraint of domain wall motion was determined: average particle size of 1m and a number of particles per unit area of 0,025/m2. The intragranular precipitation of carbide, at temperatures between 100ºC and 225ºC was the main cause of the increase on core loss. The 180ºC ageing test results have confirmed that yield strength peaks are reached quite earlier than the core loss peaks